Penerapan Mikrokontroler Pembasmi Hama Ramah Lingkungan pada Kelompok “Tani Jaya” Desa Pasir Mijen Kabupaten Demak - Khoirul Muslimin; Ali Ali; Khairul Anwar; Anandayu Sekar Purbaningrum; Elda Nur Ivana (Universitas PGRI Semarang, 2025)
Kelompok tani